Determinants of Work Engagement in Nepalese Commercial Banks - Niraula, Ganesh Prasad; Kharel, Shreekrishna (International Research Journal of MMC, 2026)
Work engagement has become an important phenomenon in this twenty-first-century business environment because the service sector is facing tough competition from within and outside of the country. To achieve a competitive advantage, engagement is necessary, which provides strength to the organization and makes it competitive. Therefore, this study aims to examine the factors determining work engagement in Nepalese commercial banks. We used a cross-sectional research design and positivist epistemology under a 95% interval and 5% margin of errors. The study collected primary data from 375 bank employees as a sample of seven commercial banks, using a stratified sampling technique with a five-point Likert scale from the employees, which includes two joint venture banks, two public limited banks, and three private commercial banks, during the first quarter of 2026. The hypothesized relationships and data were analyzed using Partial Least Squares Structural Equation Modeling (Smart-PLS). The reliability, validity, and convergent and discriminant validity were established through the same statistical software.  The findings reveal that psychological empowerment positively associates with work engagement, leadership empowerment positively associates with work engagement, and perceived organizational support also positively associates with work engagement. This study provides valuable insights to academics and professionals of banks to emphasize implementing leadership dynamics in a tactical way to promote work engagement, which is anticipated to produce two benefits: better organizational performance and better employee well-being.